2011
DOI: 10.1590/s1808-86942011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral hearing loss: benefits and satisfaction from the use of hearing aids

Abstract: A unilateral hearing loss is characterized by reduced hearing in one ear. The problems caused by sensory deprivation can be minimized with the use of hearing aids (HA). Aim:To analyze the correlation between the prescribed grain and the insertion gain difference and with the results obtained regarding the benefit and satisfaction with the use of hearing aids in unilateral hearing impaired patients. Materials and Methods:prospective study with 15 subjects, mean age of 41.6 years, of both genders, users of heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 10 publications
3
19
0
7
Order By: Relevance
“…The literature shows different and greater results, for example in the study conducted in 2010, both groups (53.8% adults and 72.2% elderlies) reported that their recent research (2011), with unilateral hearing loss carriers, verified mean values which varied in 3.53 to 4.73 points. Once again, the results are similar to this study 19 . Analyzing Table 3 and Figure 2, considering question number 1 that refers to the time of use the HA, it was confirmed the mean score of 3.73, median score of 4 and that 40.9% of the sample assigned maxim score to this question, that is, they reported to use the HA more than eight hours a day.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The literature shows different and greater results, for example in the study conducted in 2010, both groups (53.8% adults and 72.2% elderlies) reported that their recent research (2011), with unilateral hearing loss carriers, verified mean values which varied in 3.53 to 4.73 points. Once again, the results are similar to this study 19 . Analyzing Table 3 and Figure 2, considering question number 1 that refers to the time of use the HA, it was confirmed the mean score of 3.73, median score of 4 and that 40.9% of the sample assigned maxim score to this question, that is, they reported to use the HA more than eight hours a day.…”
supporting
confidence: 90%
“…The mean of answer for question 4 was 4.09 and the median was 4 point, and 45.5% of the sample reported to be very satisfied using the hearing aid, this result is a little inferior to the result found in a study developed in Rio Grande do Sul with adults (53.8%) and elderlies (52.8%) of a Hearing Health Program 20 and in another study developed in the state of São Paulo (60%) 19 . A study revealed much superior results, above 90% of the subjects satisfied.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…, and even though the loss was bilateral, but with adaptation unilateral 26 . In addition, it is noteworthy that for both groups observed satisfaction was high.…”
mentioning
confidence: 93%